Implementasi Manajemen Talenta Sebagai Upaya Membangun Aparatut Sipil Negara (ASN) Profesional di Pemerintah Kota Pontianak - Dwi Nur Handayani (Universitas Sebelas Maret, 2023)
Along with development of human resource management concept paradigm it has shifted previous perception that viewed humans only one of the factors organizational production. However, currently human aspect in organization is not limited to that, but humans are asset for organization which then develops concept of talent management. Talent management has been outlined in form regulations required all government agencies to implement, including agencies in the regions. Purpose of research is describe implementation talent management in Pontianak City Government. Qualitative descriptive is method used conducting research. Results of research found to support implementation talent management, Pontianak City Government developed an application, namely Sistem Informasi Manajemen Talenta Kota Pontianak (SIMANTAP) application. Implementation talent management in Pontianak City Government begins with analyzing talent needs to predict number of talents needed according to positions will be vacant. After analysis, identification is carried out, in this case talent mapping for categorization in talent manahement box consisting of nine categories or talent mapping carried out. Based on results assessment and then determined as a succession planning group. Talent development carried out in classical and non classical forms as well other forms development that cannot be separated from monitoring and evaluation of the Personnel Development Officier. Final stage placing talents as successors to positions that are empty or vacant.